Structure of the moon's surface - Fielder, Gilbert (Pergamon Press, 1961)
Structure of the Moon's Surface aims to assemble and marshal relevant matter, and to produce a largely unprejudiced text which brings lunar studies up to date and stresses the importance of certain features of the Moon which have frequently been disregarded in the past, largely because of lack of knowledge about them. The book contains 14 chapters organized into two parts. Part I reviews and summarizes important physical problems. These include the liberations of the moon; height determinations of points of the moon's surface; the figure of the moon; and the moon's temperature and atmosphere.